Corn silage, wheat head silage and milage for finishing cattle - Bolsen, K.K.; Conway, K.L.; Henry, P.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Six finishing rations were compared: (1) 10% corn silage, (2) 20% corn silage, (3) 10% wheat head silage, (4) 20% wheat head silage, (5) unprocessed (whole) milage and (6) processed (rolled) milage. Each ration was fed to 18 yearling steers for 123 days. Rate of gain was not affected by ration. Feed consumption and feed required per lb. of gain were higher for steers receiving whole milage than for steers receiving any of the other five rations. Although steers fed rolled milage consumed less feed, they were 11.4 percent more efficient than steers fed whole milage.
Keywords: Beef; Corn silage; Wheat silage; Milo